Diagnosis and Treatment of Gorham-Stout Disease in Maxillofacial Regions. Issue 2 (March 2018) - Qu, Luyao; Cai, Xieyi; Wang, Baoli
Abstract : Purpose: This study was aimed to investigate the clinical features, imaging examination, and treatment of the patients with Gorham-Stout disease (GSD) in maxillofacial region, so as to improve the understanding of GSD. Methods: The medical records of the patients with GSD who were referred to Shanghai Ninth People's Hospital from January 2010 to May 2016 were reviewed. Their ages, lesion location, imaging results, laboratory examination results, treatment, and therapeutic effects were analyzed. Results: A total of 4 cases were included (males 2, females 2). The average onset age was 40 years. GSD attacked the mandible in 2 cases; mandible and temporal bone in 1 case; and mandible, temporal bone, and zygoma in 1 case. All cases were examined by computed tomography (CT), which showed bone resorption and atrophy of soft tissue in involved region. Four patients were given alendronate for treatment. All of them had no significant signs of progress after treatment. Conclusions: GSD can affect one single bone or multiple bones in maxillofacial region. The diagnosis mainly depends on the imaging examinations. Enhanced CT or magnetic resonance imaging is advocated for differential diagnosis of this disease. Alendronate was used with apparent good effect in these patients.